رۆڵی رۆژنامەگەریی مۆبایل لە بەرهەمهێنانی هەواڵی كەناڵە ئاسمانییە كوردییەكان (توێژینەوەیەكی وەسفیی شیكارییە) - مستەفا, رێبەر گۆران; محەمەد, ئەركان جەبار (Sulaimani Journal for Humanities, 2022)
The aim of the current study to know the news subjects prepared by mobile for the Kurdish satellite channels and exploring the main resources Kurdish satellite channels depend on in news coverage applying mobile journalism. Moreover, observing the tasks done in news coverage while using this type of journalism. The study applies analytical descriptive method using content analysis form as an instrument which is used on purposive sample between January 1st and April 1st, 2021. The present study concludes that financial and service news are the most important subjects broadcasted through mobile journalism on Kurdish satellite channels. Simultaneously, the most important sources the Kurdish satellite channels rely on are governmental and political authorities and administrator. Finally, the channels pay attention to some task in broadcasting news, giving information is on the top.